Profil Berpikir Kritis Peserta Didik SMP pada Materi Sistem Ekskresi Manusia - Erfin Nofianti*; Ani Nurhidayanti; Novia Amarta Handayani; Dadan Rosana; Insih Wilujeng (Universitas Syiah Kuala, 2022)
Critical thinking is the ability to analyze and find out the truth of the information obtained in order to determine the right decision. The purpose of this study was to determine the critical level of class VIII students at SMP Negeri 2 Bungkal, especially on the material of the human excretory system. Type of this research is descriptive qualitative. The subjects used were students of class VIII A SMP Negeri 2 Bungkal, Ponorogo who collected 30 students using purposive sampling technique. Data collection techniques consist of interviews and tests. The research instrument consisted of a teacher interview sheet and a critical thinking question instrument that had been validated by expert lecturers. The data analysis technique used is descriptive analysis technique. The results showed that in the aspect of interpreting the average score was 34.66 (very low), analyzing 38.66 (low), evaluate 55.33 (enough), concluding 29.99 (very low), explaining 58.66 (enough). So that overall students' critical thinking is included in the low category with an average value of 43.46. This research is important because it can be used as input for teachers to design learning using appropriate models and approaches so that they can develop and improve students' critical thinking